HUBUNGAN ANTARA PENGUASAAN IDE POKOK DENGAN KEMAMPUAN MERINGKAS TEKS EKSPLANASI SISWA KELAS V SDN TAROKAN 3 TAHUN 2024 - Lioni, Jihan Nabila Permata; Endang Sri Mujiwati; Ilmawati Fahmi Imron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims (1) to determine the mastery of the main ideas of class V students at SDN Tarokan 3 in 2024; (2) to determine the ability to summarize explanatory texts of class V students at SDN Tarokan 3 in 2024; and (3) to determine the relationship between mastery of main ideas and the ability to summarize explanatory texts for fifth grade students at SDN Tarokan 3 in 2024. This research uses a quantitative approach and product moment correlation analysis techniques. The results of this research are (1) class V students of SDN Tarokan 3 in 2024 mastered the main ideas as evidenced by the Classical Learning Completeness (KBK) which was 66.66% which was categorized as high; (2) fifth grade students at SDN Tarokan 3 in 2024 were able to summarize explanatory texts as evidenced by their Classical Learning Completeness (KBK) being 76.66% which was categorized as high; and (3) there is a relationship between mastery of the main idea and the ability to summarize explanatory text for class V students of SDN Tarokan 3 in 2024 as evidenced by the results of calculations using the product moment correlation technique showing the Correlation Coefficient (r) value of the mastery of main idea variable with the ability to summarize explanatory text of 0.712 and shows that rcount > rtable, namely 0.712 > 0.361. From these results it can be seen that there is a positive relationship of 0.712 between mastery of main ideas and the ability to summarize explanatory texts for class V students at SDN Tarokan 3 in 2024.